HAK IMUNITAS ADVOKAT BERDASARKAN PASAL 16 UNDANG-UNDANG NOMOR 18 TAHUN 2003 TENTANG ADVOKAT JO PUTUSAN MAHKAMAH KONSTITUSI NOMOR 26/PUU-XI/2013, TANGGAL 14 MEI 2014 - Imron Imron (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2020)
Advocates are people who work in providing legal services, both inside and outside the court, advocates are also a noble or honorable profession, advocates have a role that is no less important than other law enforcers and has the same position as a law enforcer so that it is natural for lawyers to have the right of immunity, namely the right of immunity to the work of his profession.Advocates in carrying out their profession, cannot be prosecuted both civil and criminal in carrying out their professional duties in good faith for the benefit of the client's defense outside or in court, but in practice there are many cases involving advocates when carrying out their profession in the field up to the verdict until the verdict criminal.The problem raised in this paper is whether the lawyer is immune to the law with the existence of an advocate's immunity rights and how the legal protection of the advocate's immunity rights in carrying out his profession. This type of research is normative juridical research, library research with the problem approach used in writing this thesis is the statute approach.With the enactment of laws and regulations governing the rights of advocates of immunity, that advocates are not immune from the law but because the tasks or work done by advocates constitute the work or noble profession, then he is given special authority, namely the right of immunity or the right to immunity in law carrying out his professional duties